2015
DOI: 10.1242/jcs.167874
|View full text |Cite
|
Sign up to set email alerts
|

Mecp2 regulates neural cell differentiation by suppressing the Id1 to Her2 axis in zebrafish

Abstract: Rett syndrome (RTT) is a progressive neurological disorder caused by mutations in the X-linked protein methyl-CpG-binding protein 2 (MeCP2). The endogenous function of MeCP2 during neural differentiation is still unclear. Here, we report that mecp2 is required for brain development in zebrafish. Mecp2 was broadly expressed initially in embryos and enriched later in the brain. Either morpholino knockdown or genetic depletion of mecp2 inhibited neuronal differentiation, whereas its overexpression promoted neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…However, the neural differentiation rate in the shId1 group was higher, and 85.27% § 5.43% of transfected MSCs appeared multipolar with projections connected in a network after 48 h of neural induction, whereas only 57.38% § 2.84% and 56.39% § 5.36% of MSCs in the NC and nontransfected groups, respectively, exhibited multipolar or bipolar morphologies ( Figure 6(A)). Thus, it appears that silencing the Id1 gene can improve the neural differentiation rate of MSCs, consistent with a report that neural differentiation can be increased by suppressing Id1 expression in zebrafish [32]. It has been reported that high expression of Id1 promotes cell proliferation and inhibits cell differentiation [33,34], which is in agreement with the reports that overexpression of Id1 maintains the undifferentiated state by sustaining pluripotency markers [35] and preventing commitment to a neural fate [36].…”
Section: Neural Differentiation and Immunocytochemistrysupporting
confidence: 89%
“…However, the neural differentiation rate in the shId1 group was higher, and 85.27% § 5.43% of transfected MSCs appeared multipolar with projections connected in a network after 48 h of neural induction, whereas only 57.38% § 2.84% and 56.39% § 5.36% of MSCs in the NC and nontransfected groups, respectively, exhibited multipolar or bipolar morphologies ( Figure 6(A)). Thus, it appears that silencing the Id1 gene can improve the neural differentiation rate of MSCs, consistent with a report that neural differentiation can be increased by suppressing Id1 expression in zebrafish [32]. It has been reported that high expression of Id1 promotes cell proliferation and inhibits cell differentiation [33,34], which is in agreement with the reports that overexpression of Id1 maintains the undifferentiated state by sustaining pluripotency markers [35] and preventing commitment to a neural fate [36].…”
Section: Neural Differentiation and Immunocytochemistrysupporting
confidence: 89%
“…However, several studies have demonstrated that ectopic expression of MeCP2 represses glial differentiation but promotes neuronal differentiation in mice [45,46]. Similar results are found in zebrafish that mecp2 knockdown increases neural precursors and gliogenesis, but impairs neurogenesis [47]. On the other hand, there are studies reporting that Mecp2 binds to astrocyte-specific marker GFAP and S100B to subsequently suppress their expression, and Mecp2 knockdown accelerates glial cell differentiation with elevated expression of GFAP [48,49].…”
Section: Discussionmentioning
confidence: 62%
“…In our study, the loss of Mecp2 promoted NSCs proliferation and glial cell differentiation. Interestingly, GFAP is also a downstream target of Notch signaling and Mecp2 could interact with Notch signal pathway to regulate cell proliferation and gliogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that mecp2 knockdown led to increased proliferation of neural precursors and decreased neuronal differentiation, which were reversed by simultaneously knocking down id1 or her2 , implicating Id1-HER2 signaling as a downstream pathway (Gao et al, 2015). Another study tracked inflammatory phenotypes in mecp2 mutants over the course of development, finding decreased expression of the proinflammatory cytokine, tnfa , as early as 6 hpf, while differences in other cytokines emerge later (van der Vaart et al, 2017).…”
Section: Zebrafish Models Of Neurodevelopmental Disordersmentioning
confidence: 99%